Penyuluhan Hepatitis B dengan Pendekatan Dokter Keluarga pada Ibu Hamil di Kelurahan Pengasinan Depok - Ni Luh Aurial Widjayanti; Audrey Alvura Digna; Muhammad Kevin Auliansyah Akbar; Reinhart Fikram Imam Akbar; Muhammad Alif Farhan; Tiwuk Susantiningsih; Maria Selvester Thadeus (Segara : Jurnal Pengabdian Kepada Masyarakat, 2025)
Hepatitis B in pregnant women is a major cause of vertical transmission from mother to child and carries a high risk of developing into chronic infection. This educational activity aimed to improve family knowledge and involvement in the holistic management of pregnant women with hepatitis B through a family medicine approach. The activity was conducted in Kelurahan Pengasinan, Depok, West Java, using methods such as home visits, direct counseling, distribution of educational media, and evaluation through pre-test and post-test questionnaires. The results showed an increase in family knowledge regarding hepatitis B, the importance of antenatal screening, and the role of immunization in preventing perinatal transmission. In conclusion, the family medicine approach effectively supports educational interventions and enhances family preparedness in assisting pregnant women in managing this disease